Castles of steel : Britain, Germany, and the winning of the Great War at sea - Massie, Robert K., 1929-2019 05.01.1929-02.12.2019 (Random House, 2003)
In a work of extraordinary narrative power, filled with brilliant personalities and vivid scenes of dramatic action, Robert K. Massie, the Pulitzer Prize-winning author of Peter the Great, Nicholas and Alexandra, and Dreadnought, elevates to its proper historical importance the role of sea power in the winning of the Great War. The predominant image of this first world war is of mud and trenches, barbed wire, machine guns, poison gas, and slaughter. A generation of European manhood was massacred, and a wound was inflicted on European civilization that required the remainder of the twentieth century to heal. But with all its sacrifice, trench warfare did not win the war for one side or lose it for the other. Over the course of four years, the lines on the Western Front moved scarcely at all; attempts to break through led only to the lengthening of the already unbearably long casualty lists. For the true story of military upheaval, we must look to the sea